Efeito do co-dopante (Sr2+) e da glicose nas propriedades estruturais e ópticas do YAG dopado com íons terras raras (Eu3+, Ce3+ e Tb3+) - Silveira, Wellisson Santos (2018)
In this work, the effects caused by the glucose and of co-dopant concentrations on the structural and optical properties of the rare earth doped (TR) compound Y3Al5O12 (YAG) were investigated. To do this, were produced YAG samples, powdered, were doped with the Eu3+, Ce3+ and Tb3+ ions (YAG:Eu3+, YAG:Ce3+ and YAG:Tb3+), varying the glucose concentration, in order to study the effect of glucose in these compounds. Eu3+ doped samples were also produced and co-doped with various concentrations of Sr2+ (YAG:Eu3+,Sr2+), while maintaining the amount of glucose fixed, in order to investigate the role of the co-dopant in this material. To produce the samples was used the modified sol-gel method. The structural characterization was done by of X-ray diffraction technique (XRD) and the optical characterization by means of photoluminescence (FL) measurements. The XRD results showed that the method used was quite efficient for obtaining the compounds desired single phase. By means of the Rietveld refinement and the Scherrer equation the size of the crystallites was estimated, presenting nanometric values. For the YAG:Eu3+ compounds, the size of the crystallite was not influenced by the glucose concentration, but for the YAG:Ce3+ and YAG:Tb3+ the change in glucose concentration altered the size of the crystallite. On the YAG:Eu3+,Sr2+ samples, the crystallite size changed due to the amount of the co-dopant. In the FL excitation spectra of the YAG: Eu3+ and YAG:Eu3+,Sr2+ compounds was observed an intense broadband around 220 nm, attributed to the interaction between Eu3+ and O2-, known as charge transfer band. already the spectra of excitation YAG:Ce3+ and YAG:Tb3+ exhibited bands centered at 451 nm and 273 nm, respectively, which are attributed to transitions 4f - 5d of each dopant. The emission spectra of the YAG:Eu3+ and YAG:Eu3+, Sr2+ exhibited the most intense band around 592 nm, which is attributed to the 5D0 - 7F1 transition. For the YAG:Ce3+, the emission spectra presented a wide and intense band around 525 nm, which is attributed to the overlap of two transitions characteristic of the Ce3+ ion. On the other hand, YAG:Tb3+ emission spectra exhibited intense bands, typical of the ion, in two regions: in the region of the blue and of the green. The most intense peak is located in the blue region, around 385 nm, assigned the 5D3 - 7F6 transition. Was observed that the variation of the glucose concentration modified the FT spectra of all the YAG:TR3+ samples, as well as the Sr2+ concentration altered the spectra of the YAG:Eu3+,Sr2+.